Improving Students’ STEM Skills Through the Development of an E-Learning Chemistry Book Integrated with Sasak Local Wisdom - Devi Qurniati; Dwi Wahyudiati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop a feasible and effective e-learning chemistry book integrated with Sasak’s local wisdom to enhance students’ science, technology, engineering, and mathematics (STEM) skills. The research adopts a development approach utilizing the ADDIE model include analysis, design, development, evaluation and implementation. Product trial on chemistry education students at UIN Mataram employing a quasi-experimental pre-test and post-test control group design. The study reveals that the e-learning chemistry book, integrated with Sasak local wisdom, achieves an Aiken’s validity coefficient of 0.890, an intraclass correlation coefficient (ICC) value of 0.810, and a Cronbach’s alpha reliability value of 0.875. Furthermore, the results of the independent sample T-test indicate a significance value of 0.01, which is less than α (0.05), affirming that the e-learning chemistry book integrated with Sasak local wisdom meets valid and reliable criteria and is declared effective in enhancing students’ STEM skills